Peran Dari OSCE Minsk Group Dalam Mediasi Konflik Di Wilayah Nagorno-Karabakh - Prasada Arnaya, I Putu Angga; Anom Wiranata, I Made; Intan Prameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTRACK Ethnic conflict is one of the most frequent form s of conflict that arises after the desolation of the Soviet Union. Ethnic differences between regions in the former Soviet Union is a major cause of ethnic conflict. Nagorno-Karabakh is one of territory of the former Soviet Union that face ethnic conflict. Organisation for Security and Cooperation in Europe ( OSCE) as the world’s largest regional security thinks the need to do the mediation of Nagorno-Karabakh conflict involving Armenia and Azerbaijan through its institution, OSCE Minsk Group. OSCE Minsk Group co-chaired by United States of America, France, and Russia. This study aims to describe OSCE Minsk Group’s role as mediator in the conflict of Nagorno-Karabakh. This study assessed by using ethnonationalist and mediation as concepts within 2009-2013 as timeline. Key words: Nagorno-Karabakh, Armenia, Azerbaijan, OSCE Minsk Group